Theoretical study of cisplatin adsorption on silica - Simonetti, S. (2011)
The adsorption of cisplatin and its complexes, cis-[PtCl(NH3)2]+ and cis-[Pt(NH3)2]2+, on a SiO2(1 1 1) hydrated surface has been studied by the Atom Superposition and Electron Delocalization method. The adiabatic energy curves for the adsorption of the drug and its products on the delivery system were considered. The electronic structure and bonding analysis were also performed. The molecule–surface interactions are formed at expenses of the OH surface bonds. The more important interactions are the Cl–H bond for cis-[PtCl2(NH3)2] and cis-[PtCl(NH3)2]+ adsorptions, and the Pt–O interaction for cis-[Pt(NH3)2]2+ adsorption. The Cl p orbitals and Pt s, p y d orbitals of the molecule and its complexes, and the s H orbital and, the s and p orbitals of the O atoms of the hydrated surface are the main contribution to the surface bonds.